Nutritional Status and Blood Glucose in Adolescents: Evidence from Luwuk Banggai, Indonesia - Dwi Wahyu Balebu; Ridwan Amiruddin; Nurhaedar Jafar; A. Arsunan Arsin; Muhammad Syafar; Lalu Muhammad Saleh; Erni Yusnita Lalusu; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study was conducted to analyze the relationship between nutritional status, waist circumference, and body mass index (BMI) with fasting blood glucose levels in adolescents in South Luwuk District. The incidence of Diabetes Mellitus (DM) among adolescents has been increasing, primarily due to lifestyle and dietary changes. This research aims to fill the knowledge gap regarding the relationship between central obesity and blood glucose levels in the adolescent age group. Using a cross-sectional design, data were collected from 276 adolescents, and the analysis was carried out using the Chi-square test to identify the relationships between these variables. The results of the study indicated a significant relationship between gender, age, and BMI with blood glucose levels, while no significant relationship was found between waist circumference and blood glucose levels. This research contributes to understanding the risk factors of DM in adolescents and highlights the importance of proper nutritional interventions as preventive measures.